2012
DOI: 10.1186/1472-684x-11-17
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on care and communication involving incurably ill Turkish and Moroccan patients, relatives and professionals: a systematic literature review

Abstract: BackgroundOur aim was to obtain a clearer picture of the relevant care experiences and care perceptions of incurably ill Turkish and Moroccan patients, their relatives and professional care providers, as well as of communication and decision-making patterns at the end of life. The ultimate objective is to improve palliative care for Turkish and Moroccan immigrants in the Netherlands, by taking account of socio-cultural factors in the guidelines for palliative care.MethodsA systematic literature review was unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 54 publications
7
38
1
Order By: Relevance
“…In line with this finding, previous research has shown that overt communication about pain and sorrow between patients from certain ethnic minority groups and their relatives is limited. 34 Additionally, relatives’ high levels of hope triggered healthcare professionals, caring for patients with an uncertain prognosis, to continue life-saving treatments and reinforced their belief in their core responsibility to save patients’ lives, while these patients’ voices were largely unheard. Likewise, previous research demonstrates that more aggressive interventions occur at the end of the lives of patients from ethnic minority groups.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this finding, previous research has shown that overt communication about pain and sorrow between patients from certain ethnic minority groups and their relatives is limited. 34 Additionally, relatives’ high levels of hope triggered healthcare professionals, caring for patients with an uncertain prognosis, to continue life-saving treatments and reinforced their belief in their core responsibility to save patients’ lives, while these patients’ voices were largely unheard. Likewise, previous research demonstrates that more aggressive interventions occur at the end of the lives of patients from ethnic minority groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, duration of the illness, number of hospitalizations, caregiver satisfaction with hospitalization and staff are factors potentially related to caregiver impact for further study. None of the reviewed studies examined the impact of these factors on caregivers’ reactions, whereas research on caregivers of individuals hospitalized for non-psychiatric reasons showed negative impacts on caregivers including financial burden (42), caregiver-patient relationship quality (43), and patient-functioning and caregiver support (44). Third, greater understanding of the heterogeneity in impact of psychiatric hospitalizations on caregivers with a focus on characteristics of patient’s illness (e.g., duration of illness, patient’s age, degree of risk for harm) is needed.…”
Section: Discussionmentioning
confidence: 99%
“… 4 This is especially important because care professionals in Western countries experience difficulties giving palliative care to patients with a migration background. 13 16 …”
Section: Introductionmentioning
confidence: 99%